USE OF EARTHWORM TO INCREASE UPLAND ULTISOLS PRODUCTIVITY - SUBOWO, .; ANAS, I.; DJAJAKIRANA, G.; ABDURACHMAN, A.; HARDJOWIGENO, S. (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2002)
Research conducted to identify the habitat and population of earthworm in upland Ultisols, was to study the effect of ameliorant (lime and organic matter) on Ultisols as earthworm habitat in simple bamboo house experiment, to evaluate the activity of earthworm (Pheretima hupiensis) atvarious ameliorant amandment in a terrarium, the use of earthworm to increase soybean yield on Typic Palehumults. The results showed that earthworm population in Ultisols was dominated by P. hupiensis. The constraints of P. hupiensis population in wet season are low P2O5 content and high soil surface temperature at noon time. In transition from wet to dry season the constraints are high soil strength and C:N ratio soil organic matter. In dry season the constraint is low availability of water. No tillage with vertical application of organic matter and lime was the best treatment to improve the P. hupiensis activities in the argillic horizon. P. hupiensis decrease argilic horizon bulk densities, deposits casting around the rhizosfer area to improve soil nutrients absorbtion; hence, increase the upland Ultisols productivity. Population of P. hupiensis has a positive significant correlation with soybean var. Willis growth in upland Typic Palehumults with 1.19 g/ml bulk density and 12 cm-deep argillic horizon.